Fiscal Decentralization, Basic Public Service Spending, And Poverty - Yusuf, Muhammad (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Fiscal decentralization has been widely promoted as a policy instrument to improve public welfare and reduce poverty by granting greater fiscal autonomy to local governments. However, empirical evidence on the relationship between fiscal decentralization and poverty remains inconclusive, and the mechanisms through which fiscal decentralization influences poverty outcomes are still insufficiently explored. This study investigates the direct effect of fiscal decentralization on poverty and examines the mediating role of expenditure allocation for basic services in Indonesia. Using provincial-level panel data covering 34 provinces from 2007 to 2024, this study employs Structural Equation Modeling (SEM) to analyze both direct and indirect relationships among the variables. Fiscal decentralization is measured by the ratio of local own-source revenue to total local expenditure, while expenditure allocation for basic services consists of spending on education, health, public works and housing, public order and safety, environmental protection, and social protection. The results indicate that fiscal decentralization significantly increases expenditure allocation for basic services and directly reduces poverty. In addition, expenditure allocation for basic services significantly contributes to poverty reduction and partially mediates the relationship between fiscal decentralization and poverty. These findings suggest that the effectiveness of fiscal decentralization in alleviating poverty depends not only on the degree of fiscal autonomy but also on how local governments allocate resources toward essential public services. This study contributes to the fiscal decentralization literature by providing empirical evidence on the expenditure channel through which fiscal decentralization influences poverty outcomes in Indonesia. The findings offer important policy implications for strengthening poverty reduction strategies through improved fiscal governance and more effective allocation of local government expenditures.